Differential geometry of the q-plane - Çelik, SA; Çelik, S (WORLD SCIENTIFIC PUBL CO PTE LTD, 2000)
Hoof algebra structure on the differential algebra of the extended q-plane is defined. An algebra of forms which is obtained from the generators of the extended q-plane is introduced and its Hopf algebra structure is given.
Keywords: CALCULUS; Physics